Use of an invertebrate animal model (Aplysia californica) to develop novel neural interfaces for neuromodulation - Zhuo, Junqi; Gill, Jeffrey P.; Jansen, E. Duco; Jenkins, Michael W.; Chiel, Hillel J. (Frontiers in Neuroscience, 2022)
New tools for monitoring and manipulating neural activity have been developed with steadily improving functionality, specificity, and reliability, which are critical both for mapping neural circuits and treating neurological diseases. This review focuses on the use of an invertebrate animal, the marine mollusk Aplysia californica, in the development of novel neurotechniques. We review the basic physiological properties of Aplysia neurons and discuss the specific aspects that make it advantageous for developing novel neural interfaces: First, Aplysia nerves consist only of unmyelinated axons with various diameters, providing a particularly useful model of the unmyelinated C fibers in vertebrates that are known to carry important sensory information, including those that signal pain. Second, Aplysia’s neural tissues can last for a long period in an ex vivo experimental setup. This allows comprehensive tests such as the exploration of parameter space on the same nerve to avoid variability between animals and minimize animal use. Third, nerves in large Aplysia can be many centimeters in length, making it possible to easily discriminate axons with different diameters based on their conduction velocities. Aplysia nerves are a particularly good approximation of the unmyelinated C fibers, which are hard to stimulate, record, and differentiate from other nerve fibers in vertebrate animal models using epineural electrodes. Fourth, neurons in Aplysia are large, uniquely identifiable, and electrically compact. For decades, researchers have used Aplysia for the development of many novel neurotechnologies. Examples include high-frequency alternating current (HFAC), focused ultrasound (FUS), optical neural stimulation, recording, and inhibition, microelectrode arrays, diamond electrodes, carbon fiber microelectrodes, microscopic magnetic stimulation and magnetic resonance electrical impedance tomography (MREIT). We also review a specific example that illustrates the power of Aplysia for accelerating technology development: selective infrared neural inhibition of small-diameter unmyelinated axons, which may lead to a translationally useful treatment in the future. Generally, Aplysia is suitable for testing modalities whose mechanism involves basic biophysics that is likely to be similar across species. As a tractable experimental system, Aplysia californica can help the rapid development of novel neuromodulation technologies.